Emerging Prospects for Nanoparticle-Enabled Cancer Immunotherapy - Manal Ali Buabeid; El-Shaimaa A. Arafa; Ghulam Murtaza (Journal of Immunology Research)
One of the standards for cancer treatment is cancer immunotherapy which treats both primary and metastasized tumors. Although cancer immunotherapeutics show better outcomes as compared with conventional approaches of cancer treatment, the currently used cancer immunotherapeutics have limited application in delivering cancer antigens to immune cells. Conversely, in solid tumors, tumor microenvironment suppresses the immune system leading to the evasion of anticancer immunity. Some promising attempts have been made to overcome these drawbacks by using different approaches, for instance, the use of biomaterial-based nanoparticles. Accordingly, various studies involving the application of nanoparticles in cancer immunotherapy have been discussed in this review article. This review not only describes the modes of cancer immunotherapy to reveal the importance of nanoparticles in this modality but also narrates nanoparticle-mediated delivery of cancer antigens and therapeutic supplements. Moreover, the impact of nanoparticles on the immunosuppressive behavior of tumor environment has been discussed. The last part of this review deals with cancer immunotherapy using a combination of traditional interventional oncology approach and image-guided local immunotherapy against cancer. According to recent studies, cancer therapy can potentially be improved through nanoparticle-based immunotherapy. In addition, drawbacks associated with the currently used cancer immunotherapeutics can be fixed by using nanoparticles.